INDONESIA EFFORT TO ATTRACTING INVESTMENT IN TOURIST DESTINATION DEVELOPMENT - Parlindungan, Henky Hotma; Manurung, Hendra (Jurnal Industri Parawisata, 2023)
This study aims to discuss Indonesia implemented strategy in optimizing effort in strengthening and enhance collaboratively to get investment. In fact, Indonesia's economic growth in 2020 had experienced a contraction due to the outbreak of the COVID-19 pandemic. At that time, the second-quarter decreased and gradually recovered in the third and fourth quarters. In the second quarter of 2021, Indonesian economic growth hit around seven percent. A thriving and financially sound capital market helps and supports the country's economic growth and can enhance inter-community cooperation. The factors for developing tourism companies and the creative economy of the 21st century are structured management, use of high-technology, employee skills and capital adequacy. However, Indonesia’s market opportunities in tourist destinations are still increasingly generated and have become the capital for promoting to foreign investors interested in realizing their investments. This research reveals the improving of investment of the tourism sector and the creative economy supporting Indonesia's economic growth is promising challenges.